2008
DOI: 10.1016/j.brainres.2008.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Summing it up: Semantic activation processes in the two hemispheres as revealed by event-related potentials

Abstract: The coarse coding hypothesis suggests that semantic activation is broader in the right hemisphere, affording it an advantage over the left hemisphere for the activation of distantly related concepts or multiple meanings of lexically ambiguous words. Behavioral studies investigating coarse coding have yielded mixed results, perhaps in part because such measures sum across multiple processing stages. To more directly tap into the semantic activation processes that are the focus of the coarse coding hypothesis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
15
0
1
Order By: Relevance
“…If the right hemisphere does this, it might explain some of its apparent difficulty in response selection, as seen in commissurotomized patients performing poorly in verification tasks for problems presented to the right hemisphere (e.g., Funnel et al, 2007). However, in the language domain, multiple direct tests of the coarse coding hypothesis have failed to find support for it (Kandhadai and Federmeier, 2007, 2008). Also problematic for this view is that one might have expected to see earlier effects of relatedness on the P300 in the right hemisphere, reflecting a lack of focus on the correct answer as a target item, which is not what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…If the right hemisphere does this, it might explain some of its apparent difficulty in response selection, as seen in commissurotomized patients performing poorly in verification tasks for problems presented to the right hemisphere (e.g., Funnel et al, 2007). However, in the language domain, multiple direct tests of the coarse coding hypothesis have failed to find support for it (Kandhadai and Federmeier, 2007, 2008). Also problematic for this view is that one might have expected to see earlier effects of relatedness on the P300 in the right hemisphere, reflecting a lack of focus on the correct answer as a target item, which is not what we observed.…”
Section: Discussionmentioning
confidence: 99%
“…But more broadly, involvement of the RH in language comprehension is not only not maladaptive, it is normal and essential. Thus, as we consider hemispheric asymmetries in print specialization and how those interact with reading ability, it is important to note that RH involvement in reading is not always a sign of disorder -in fact the RH is clearly involved in many advanced reading functions in normal readers, such as integrating incoming text with sentence or discourse context (e.g., Federmeier, 2007;Federmeier & Kutas, 1999;Wlotko & Federmeier, 2007), resolving lexical and semantic ambiguities (Kandhadai & Federmeier, 2008, and interpreting non-literal language, as in jokes (Coulson & Williams, 2005). Further, in reading disorders besides dyslexia, such as alexia, RH compensation is associated with recovery (e.g., Cohen et al, 2003).…”
Section: Characteristics Of Rh Use In Readingmentioning
confidence: 99%
“…According to the total average ERPs in the lexical decision and the recognition test, we examined the source results of 300-900 ms and found the activation region was similar. Based on the previous literature [13][14][15] and the analysis of ERP component data, we chose relevance data at 400 ms and 600 ms in the lexical decision and the recognition test to make location analysis, shown in Figure 5. Table 3 displayed the Talairach coordinates of each source generator based on the low-resolution current density reconstruction.…”
Section: The Statistical Analysis Of Erps Datamentioning
confidence: 99%
“…ERP results in a large number of semantic researches revealed that the N400 effect was found [13][14][15] in the semantic processing of various words. For example, in a variety of experimental tasks on concrete and abstract words [13,15] , the experimenters found that N400 of concrete words was more negative than that of abstract words during 300-500 ms.…”
mentioning
confidence: 98%